Das Ende der kolonialen Epoche im Himalaya - Anna Okopińska (Góry, Literatura, Kultura)
An exceptional class of mountain people has emerged in recent years among the indigenous inhabitants of the highland regions of Asia. Since the 17th century, the local mountain dwellers were hired by Westerners to serve on exploratory expeditions as porters and pack animal drivers. The best among them worked as high-altitude porters in climbing expeditions to the highest peaks of Himalaya and Karakoram, where they gained mountaineering experience and technical skills. As residents of high-altitude settlements experienced in pastoral and hunting activities in the surrounding mountains, they had a natural physical advantage over Westerners. However, for many years, they only served as low-paid labourers. Their subservient mentality inherited from colonial times and a lack of confidencein their own abilities served as obstacles to social advancement. However, they managed to overcome this! Currently, local mountain dwellers have taken complete control of high-altitude tourism.